Development of an accelerated leaching method for incineration bottom ash correlated to toxicity characteristic leaching protocol - Lin, Shengxuan (2016)
Heavy metals and some metalloids are the most significant inorganic contaminants specified in toxicity characteristic leaching procedure (TCLP) in determining the safety of landfills or further utilization. As a consequence, a great deal of efforts had been made on the development of miniaturized analytical devices, such as Microchip Electrophoresis (ME) and μTAS for on-site testing of heavy metals and metalloids to prevent spreading of those pollutants or decrease the reutilization period of waste materials such as incineration bottom ash. However, the bottleneck lied in the long and tedious conventional TCLP that requires 18 h of leaching. Without accelerating the TCLP process, the on-site testing of the waste material leachates was impossible. In this study, therefore, a new accelerated leaching method (ALM) combining ultrasonic assisted leaching with tumbling was developed to reduce the total leaching time from 18 h to 30 min. After leaching, the concentrations of heavy metals and metalloids were determined with ICP-MS or ICP-optical emission spectroscopy. No statistical significance between ALM and TCLP was observed for most heavy metals (i.e., cobalt, manganese, mercury, molybdenum, nickel, silver, strontium, and tin) and metalloids (i.e., arsenic and selenium). For the heavy metals with statistical significance, correlation factors derived between ALM and TCLP were 0.56, 0.20, 0.037, and 0.019 for barium, cadmium, chromium, and lead, respectively. Combined with appropriate analytical techniques (e.g., ME), the ALM can be applied to rapidly prepare the incineration bottom ash samples as well as other environmental samples for on-site determination of heavy metals and metalloids.